Effects of curcumin on metabolic and systemic diseases: Narrative review (Revista Médica de Trujillo, 2024)
In recent years, the great role of nutrition on general health has been demonstrated, specifically, polyphenols in relation to the treatment of metabolic and systemic diseases. Curcumin, a substance extracted from turmeric and proposed as a treatment for various diseases due to its diverse properties. The bibliographic search was done in both Spanish and English with the keywords: "curcumin", "metabolic diseases", "systemic diseases" in Pubmed, Embase and Cochrane and Scholar Google. Curcumin is a polyphenol found in turmeric, which has been shown to have antioxidant, anti-inflammatory, hepatoprotective and antidiabetic properties. Its influence has been seen in metabolic syndrome, type 2 diabetes mellitus, lupus, rheumatoid arthritis and psoriasis. Conclusions: This narrative review summarizes the influence of curcumin supplementation on various pathologies, in addition to certain general aspects.
Keywords: curcumin; metabolic diseases; systemic diseases; nutrition